WHY SHOULD WE PERFORM EXTENDED SURGERIES FOR CERVICAL CANCER? - L. Ungar; V. M. Nechushkina (Сибирский онкологический журнал)
A surgical technique for the complete removal of the connective tissue content of the pelvis was introduced in 1993 to improve oncological outcome of the surgical treatment of operable cervical cancer by reducing the risk of recurrence from the pelvis. Our results suggest that complete excision of the connective tissue content of the pelvis provides equal or better survival chances without any adjuvant treatment for almost 90 % of operable stage IB cervical cancer patients than less radical surgery with or without adjuvant treatment.